1999
DOI: 10.1590/s0034-71081999000400003
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of some limnological characteristics in pacu (Piaractus mesopotamicus) culture tanks as function of handling

Abstract: In order to study the water quality in fish tanks, a 166-day (January to July 1992) experiment was realized using the indigenous species "p acu" (Piaractus mesopotamicus). Two different protein levels were tested in the diet (16% and 34% crude protein) and three stocking densities (0.25, 0.50 and 0.77 fish/m2). From the results, it was observed that the interactions between stocking density and experiment length affected the characteristics bicarbonate and alkalinity, as well as the interaction between stockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
4
2
1
Order By: Relevance
“…These values were higher than the ones obtained (5.1 to 8.7 µg L -1 ) in pacu ponds (Sipaúba-Tavares et al, 1999), and lower than the ones obtained during tambaqui grow out in highly fertilized ponds (296 µg L -1 ) (Teichert-Coddington, 1996). The results show that fertilization is an unnecessary procedure, mainly in ponds that receive fish ration.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…These values were higher than the ones obtained (5.1 to 8.7 µg L -1 ) in pacu ponds (Sipaúba-Tavares et al, 1999), and lower than the ones obtained during tambaqui grow out in highly fertilized ponds (296 µg L -1 ) (Teichert-Coddington, 1996). The results show that fertilization is an unnecessary procedure, mainly in ponds that receive fish ration.…”
Section: Resultscontrasting
confidence: 61%
“…Mean observed values were from 0.24 to 0.36 mg L -1 (Table 3), which is in the fish comfort zone (Boyd & Tucker, 1998). Sipaúba-Tavares et al (1999) found lower ammonia values (0.07-0.180 mg L -1 ) than the ones in the present work, in experiments with pacu, Piaractus mesopotamicus, probably due to the lower biomass. With higher biomass, Seok et al (1995) found ammonia values between 0.47 and 1.11 mg L -1 in channel catfish.…”
Section: Resultscontrasting
confidence: 51%
“…Ammonia is the main nitrogenous waste material produced from amino acid catabolism; in water, ammonia is reduced to NO 2 -by nitrifying bacteria before its conversion into nitrate (Costa et al, 2004). The concentration of NO 2 -is usually low (0.03 -0.1 mg.L -1 ) in tropical fish culture systems with low stocking density (Sipaúba-Tavares et al, 1999;Andrade et al, 2007), but an imbalance in either ammonia production or NO 2 -conversion to nitrate can cause NO 2 -buildup (Jensen, 2003). High NO 2 -levels may develop in aquaculture systems due to high fish density (Hargreaves, 1998) or due to fertilizers added to the water (Lewis & Morris, 1986).…”
mentioning
confidence: 99%
“…When the quality of the pond water is poor it is common to occur an intensive increase of the water flow, thus reducing the residence time and consequently quickly releasing organic matter, inorganic salt, nutrients, plankton, among other components of the pond that might be damaging the production at that moment, therefore the flow control prevented the growth of phytoplankton [18]. The constant inflow and outflow in a short residence time and the uncontrolled management of rationing and supply water are some of the factors that directly influence the dynamics of nutrients.…”
Section: Discussionmentioning
confidence: 99%